Duplicated receptors for VIP and PACAP VPAC 1 R and PAC 1 R in a teleost fish, Fugu rubripes - Cardoso, João CR (2014)
Two principal groups of receptors orthologous with human PAC1R and VPAC1R and were identified and characterised at the genomic level in the teleost fish Fugu rubripes. An additional group orthologous with VPAC2R was also identified and partially characterised. In Fugu, gene duplication of each of the PAC1Rs, VPAC1Rs and VPAC2Rs appears to have occurred. The topology of the tree surrounding the Fugu duplications and other isolated piscine sequences indicates that the duplication events for these six genes clearly preceded the speciation event leading to the Cypriniformes and Tetraodontiformes and is probably teleost-specific. Overall, the combined pattern of gene expression for each pair of duplicated genes mirrored the expression in other vertebrates. However, within each pair of duplicates further specialisation had occurred, with each demonstrating differential tissue distribution profiles suggesting they that may be responsible for the divergent action of the ligands, vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating peptide (PACAP). The Fugu VPAC1R gene regions showed conserved synteny with human chromosome 3p21·3 and also C. elegans chromosome X, indicating that the putative ancestral human chromosome 3 region may be equivalent to chromosome X in Caenorhabditis elegans.